Contamination-free suspended graphene structures by a Ti-based transfer method. (July 2016) - Matruglio, Alessia; Nappini, Silvia; Naumenko, Denys; Magnano, Elena; Bondino, Federica; Lazzarino, Marco; Dal Zilio, Simone
Abstract: Minimization of contamination associated with the graphene transfer process from the growth substrate to the device surface is a major requirement for large scale CVD graphene device applications. The most widespread transfer methods are based on the use of a thin sacrificial polymeric layer such as poly(methyl methacrylate), but its complete removal after transfer is an unsolved problem; this issue is critical for suspended graphene, since the back surface often results contaminated by the dissolved polymer. Here we present a polymer-free method of commercial CVD-grown graphene transfer from the initial copper substrate to the silicon device, in which a 15 nm-thick titanium layer replaces completely the polymer film as supporting layer during the transfer process. Our approach reduces significantly the level of contaminations for supported and suspended graphene layers. Raman spectroscopy was used to prove the quality of the transferred graphene, not affected by this approach. X-ray photoelectron spectroscopy and X-ray absorption spectroscopy were used to assess the amount of the contaminants left by the transfer process. Overall carbon contamination was reduced by a factor 2, while contaminations originating from the metal etching in hydrofluoric acid, namely titanium and fluorine, were absent within the sensitivity of the used techniques.